In search of the causes of evolution : from field observations to mechanisms - Grant, Peter R., 1936-; Grant, B. Rosemary (Princeton University Press, 2010)
From the publisher. Evolutionary biology has witnessed breathtaking advances in recent years. Some of its most exciting insights have come from the crossover of disciplines as varied as paleontology, molecular biology, ecology, and genetics. This book brings together many of today's pioneers in evolutionary biology to describe the latest advances and explain why a cross-disciplinary and integrated approach to research questions is so essential. Contributors discuss the origins of biological diversity, mechanisms of evolutionary change at the molecular and developmental levels, morphology and behavior, and the ecology of adaptive radiations and speciation. They highlight the mutual dependence of organisms and their environments, and reveal the different strategies today's researchers are using in the field and laboratory to explore this interdependence. Peter and Rosemary Grant-renowned for their influential work on Darwin's finches in the Galapagos-provide concise introductions to each section and identify the key questions future research needs to address.